Cocaine and Volatile Nitrite–Induced Methemoglobinemia; a Case Report and Treatment Approach Review - Ribeiro Paixão, Milena; Accorsi, Tarso Augusto Duenhas; Prada, Luis Felipe Lopes; Pocebon, Lucas Zoboli; De Amicis Lima, Karine; Köhler, Karen Francine; Santini Echenique, Leandro; de Souza Júnior, José Leão (Archives of Academic Emergency Medicine, 2022)
Cyanosis is typically a sign of a potentially life-threatening condition in the emergency department and requires immediate workup and treatment. This case report highlights the diagnostic reasoning and clinical approach to cocaine- and volatile nitrite–induced methemoglobinemia (MHG). MHG is a rare, life-threatening cause of cyanosis. The diagnosis must be suspected in the emergency department in the presence of hypoxia and cyanosis disproportionate to cardiopulmonary repercussions and refractory to oxygen supplementation. Acquired causes are more prevalent than genetics, and recreational drugs should be highly suspected. Despite the rarity of this situation, cyanosis precipitants and the specificities of each hemoglobinopathy are reviewed in this article.